On Some Problems of Criminal Law Regulation of the Situation Change in Russia, Mongolia and China - A. V. Kuznetsov; Yingchun Sun (Сибирское юридическое обозрение, 2013)
The article deals with the analysis of the criminal law regulations in the Russian Federation, Mongolia, specifying the cause for release from criminal responsibility and punishment in consequence of some situation changes. The analysis of the CVR criminal law compromise institute norms has been conducted. The legal premises of criminal law legislation concerning the cause of release from punishment in consequence of the situation change in the criminal law of the CVR have been distinguished.